Towards an Embodied Understanding of Performing Practices. A Gestural Analysis of Debussy’s “Minstrels” According to the 1912 Piano Rolls - Ho, Jocelyn (Revue musicale OICRM)

(untitled) (OICRM, 2014)
Claude Debussy’s performance of “Minstrels” from Preludes, Book I, in the 1912 piano rolls contains expressive techniques that are not often heard today: random pushes and pulls of tempi, flippant rhythmic alterations, frequent inégale, and tempo rubato. These performing practices, although odd-sounding to the modern listener, were common at the turn of the twentieth century. His vivid rendition of the piece, including these expressive techniques that are missing from the notation, significantly alters the experience of the music. Unexpected meanings that cannot be deduced from studying the score alone arise when taking into consideration Debussy’s interpretation as a performer. This article gives an integrative analysis that regards the score and Debussy’s performance as equally important in a structural analysis. The concept of gesture is useful here, as it can be construed in both a score-based and a performative or physical approach. Moreover, in “Minstrels,” an extra dimension of physical gesture exists in its allusion to the blackface minstrel show. In the analysis, active, bodily-based concepts drawn from the blackface minstrel show are used to describe gestures and their transformations. From a Merleau-Pontyian perspective, the analysis thus treats gesture as at once musical and physical, moving away from a traditional, cognitive-based approach. The analysis shows the emergence of two large-scale structural processes—that of disorientation and that of upward reaching. These two processes culminate in the expressif section but are undercut by a dominating gesture of incoherence. A closer historical reading of the ridiculed, male “black” body in the context of blackface minstrelsy reveals that the emergent gesture-based structure of the piece can afford socio-historical meanings. The convergence between the study of historical performing practices and embodied gestural analysis yields fresh, important insights into the structure, inner workings and cultural significances of Debussy’s music.